Introduction of Takaful (Islamic Insurance) as a Potential Business Model in Indian Market - Mohd Owais; Ali, Jawwad; Hassan, Rusni (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Globalization has prompted many companies to invest in foreign markets, as a result of which many countries are implementing business models that appeal to investors. Takaful is one type of Islamic insurance system that has proved to be highly popular in Muslim nations. Many individuals who intend to start a new venture will benefit from this type of business model, which has also gained popularity in non-Muslim nations. This paper will analyze the suitability of Takaful to be introduced as a business model in India. This study adopts a mixed method of quantitative and qualitative analysis using surveys and interviews. The number of respondents selected was 50 for quantitative analysis with the target participants being people of India through social media and LinkedIn. Apart from that, for Qualitative analysis employees related to insurance companies in Malaysia were selected to assess their points of view of the Indian insurance market. The conclusion reveals that the Indian market is suitable and favorable for the Takaful business model irrespective of religion, people are willing to accept the model. Hence it is recommended that the model be introduced in the Indian market. Originality/Value: Unlike prior research, which focuses primarily on Muslim nations, this study provides valuable insights for policymakers and industry stakeholders in non-Muslim countries. Our findings underscore the potential viability of Takaful in India, emphasizing its inclusive nature and ability to cater to diverse insurance needs. Overall, this paper offers a fresh perspective on Islamic finance and the adaptation of innovative business models in emerging markets.